Modelling nitrogen-oxygen dynamics in the central Arabian Sea: Large-scale meridional structure and seasonal variations. (August 2019) - Beckmann, Aike; Hense, Inga
Abstract: The oxygen minimum zone (OMZ) of the central Arabian Sea is investigated with a biogeochemical model that couples the marine nitrogen and oxygen cycles and includes euphotic, aphotic, aerobic and anaerobic processes. The model is used to quantify the strength, location and relative timing of governing processes, in particular, nitrite generation, nitrogen losses and oxygen consumption. In an idealized two-dimensional physical environment the model is able to reproduce the observed meridional-vertical structure of oxygen and nitrate, as well as the secondary nitrite maximum layer. Characteristic features of vertical profiles are well represented and the modelled nitrogen transformation rates are in good agreement with observed values. The model results show that (i) the OMZ is neither vertically nor horizontally homogeneous, (ii) minute differences in oxygen concentration determine the thickness of the nitrite layer, (iii) there is hardly any seasonal cycle in the extent of the OMZ but a pronounced seasonal cycle in nitrite, and (iv) the nitrogen loss in the OMZ is accomplished by a succession of denitrification and anammox, based on the seasonal supply of labile detritus. We conclude that the nitrogen loss in the Arabian Sea can only be understood by taking into account the diversity, vertical arrangement and temporal succession of microbial processes.